Progress and trends in publication of oral and video presentations at the society of gynecologic oncology annual meeting from 2006 to 2016 - Anthony A. Milki; Joshua G. Cohen; Amandeep Kaur Mann; Daniel S. Kapp; John K. Chan (Elsevier, 2021)
Previous research has identified factors associated with publication of plenary presentations at the Society of Gynecologic Oncology annual meeting. However, there are no detailed comprehensive trends analyses on the publications of these oral and video presentations over time. In this analysis of 11 annual meetings, we found an increase in clinical rather than translational science publications over time. There was a greater focus on chemotherapy clinical studies and palliative care medicine, with a corresponding decline in publications on surgery. Furthermore, the time interval from presentation to publication shortened over our study period. The evaluation of trends in research publications can inform clinicians and researchers about the quality, competitiveness, and neglected areas of study from national meeting presentations.